2022
DOI: 10.1073/pnas.2211310119
|View full text |Cite
|
Sign up to set email alerts
|

NAD + metabolism drives astrocyte proinflammatory reprogramming in central nervous system autoimmunity

Abstract: Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system (CNS). Astrocytes are the most abundant glial cells in the CNS, and their dysfunction contributes to the pathogenesis of MS and its animal model, experimental autoimmune encephalomyelitis (EAE). Recent advances highlight the pivotal role of cellular metabolism in programming immune responses. However, the underlying immunometabolic mechanisms that drive astrocyte pathogenicity remain elusive. Nicotinamide adenine dinucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 87 publications
1
5
0
Order By: Relevance
“…We identified a unique sUA-CD38 interaction in this study, highlighting the physiologically essential role of sUA as a purine metabolite in sustaining life. Accumulated data suggest a remarkable overlap between the effects of sUA (8-10, 15-20, 45, 46) and CD38 inhibition/KO (21, 23, 67, 68) in counteracting inflammation, aging, and certain diseases, which also strongly supports our current findings. It should be noticed that we used an exogenous compound as the background in mice to mimic the deficiency of uricase in humans, and tissue sUA levels were unchanged after sUA supplementation, suggesting some of the limitations in our models when evaluating the physiological relevance.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We identified a unique sUA-CD38 interaction in this study, highlighting the physiologically essential role of sUA as a purine metabolite in sustaining life. Accumulated data suggest a remarkable overlap between the effects of sUA (8-10, 15-20, 45, 46) and CD38 inhibition/KO (21, 23, 67, 68) in counteracting inflammation, aging, and certain diseases, which also strongly supports our current findings. It should be noticed that we used an exogenous compound as the background in mice to mimic the deficiency of uricase in humans, and tissue sUA levels were unchanged after sUA supplementation, suggesting some of the limitations in our models when evaluating the physiological relevance.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, our findings also provide biological evidence for the neuroprotection of sUA. It has been reported that CD38 is involved in neurodegenerative diseases (67, 68), thus, sUA in central nervous system (CNS) tissues may directly inhibit CD38 activity to limit neuroinflammation and the progression of such diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the expression of CD38 is elevated in multiple tissues and cell types during aging, which is largely attributable to its induction by SASP 11 , 27 . Additionally, CD38 is upregulated in the heart following ischemia–reperfusion injury, the CNS in a variety of neurodegenerative and neuroinflammatory diseases, in tumorigenesis, and in muscle, liver and articular cartilage during aging 11 , 31 , 53 , 54 .…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence to suggest that placental mitochondrial dysfunction may be a common feature across all PE subclasses [8], however a lack of subclass-specific research endeavours has limited our current understanding of this pathology, specifically in the context of inflammation-driven PE. In non-pregnant populations, several inflammatory disease conditions have been tightly linked to mitochondrial dysfunction, in large part driven by profound overactivity of nicotinamide adenine dinucleotide (NAD + ) consuming enzymes, leading to depletion of intracellular NAD + stores [16][17][18][19][20][21][22][23][24][25][26][27][28]. In the current study, this body of work will be expanded to determine if NAD + depletion may likewise initiate placental mitochondrial dysfunction in inflammation-mediated PE.…”
Section: Introductionmentioning
confidence: 99%